Malaria attributable to one-third of anemia cases among febrile children in Eastern Uganda: A cross-sectional study - Benson Okongo; Enoch Muwanguzi; Daisy Asiimwe; Robert Wagubi; Elizabeth Alfred John; Clinton Olong (Journal of Hematology and Allied Sciences, 2026)
Objectives: The study aims to determine the Prevalence of anemia and its association with malaria infection among febrile children under 15 years at Bududa General Hospital, Eastern Uganda. Material and Methods: A hospital-based cross-sectional study was conducted among 347 febrile children between April and June 2023. Venous blood samples were collected for complete blood count and malaria microscopy. Stool samples were examined for intestinal helminths. A structured questionnaire was used to collect sociodemographic data. Multivariate logistic regression was used to identify factors associated with anemia. A P ≤ 0.05 was considered statistically significant. Results: The overall Prevalence of anemia was 225 (64.8%). The Prevalence of malaria parasitemia was 162 (46.7%), with Plasmodium falciparum as the dominant species (83.3%). Multivariate analysis revealed that malaria infection (adjusted odds ratio [aOR] = 8.24; 95% confidence interval [CI]: 3.63–18.70; P < 0.001), children aged 1–5 years (aOR = 0.24; 95% CI: 0.08–0.72; P = 0.011) and 6–10 years (aOR = 0.19; 95% CI: 0.05–0.66; P = 0.009) and a parent/guardian with secondary education (aOR = 0.40; 95% CI: 0.20–0.82; P = 0.012) were associated with anemia. The Prevalence of intestinal helminths was low (2.9%) and not associated with anemia. Conclusion: This study links a high anemia rate in febrile children to malaria, particularly affecting infants and those with less-educated caregivers, necessitating combined malaria and nutrition interventions.
Keywords: Anemia; Children; Febrile illness; Malaria; Plasmodium falciparum